2015
DOI: 10.1177/1010539515588943
|View full text |Cite
|
Sign up to set email alerts
|

Return for Postpartum Oral Glucose Tolerance Test Following Gestational Diabetes Mellitus

Abstract: A cross-sectional study was conducted to assess the prevalence and characteristics of women who received a postpartum oral glucose tolerance test and to examine barriers as reported by women who failed to return for the test. Data were collected using a mobile phone-based short messaging service. Only 352 (81.9%) women returned for the test. Women who failed to return for the test were younger (30.1 vs 32.1, P = .003) and did not have a previous history of gestational diabetes (93.6% vs 84.9%, P = .043) compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Whilst up to 18.2% of mothers screened are diagnosed with dysglycemia ( 10 ), the uptake of post-partum diabetes screening within the recommended window is suboptimal and varies widely across populations. A study conducted in England identified the uptake rate to be 17% ( 11 ), as compared to 81.9% in a Malaysian hospital ( 12 ). Unpublished data from a tertiary care institution in Singapore shows that just over half (54%) of mothers with GDM underwent post-partum diabetes screening within the recommended time frame.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst up to 18.2% of mothers screened are diagnosed with dysglycemia ( 10 ), the uptake of post-partum diabetes screening within the recommended window is suboptimal and varies widely across populations. A study conducted in England identified the uptake rate to be 17% ( 11 ), as compared to 81.9% in a Malaysian hospital ( 12 ). Unpublished data from a tertiary care institution in Singapore shows that just over half (54%) of mothers with GDM underwent post-partum diabetes screening within the recommended time frame.…”
Section: Introductionmentioning
confidence: 99%
“…The return rate for ppOGTT in our cohort was 62.2%, which is above the average reported in most studies. In a study conducted in another South East Asian country, the reported ppOGTT rate was 81.9% [28]. However, this was based on response rates collected via short message system (SMS) from patients, rather than data obtained from actual follow-up appointments.…”
Section: Discussionmentioning
confidence: 99%
“…There was a lack of statistical significance in the other variables studied such as age, BMI, family history of diabetes, type of treatment and mode of delivery in predicting the likelihood of returning for ppOGTT. Many reasons have been cited for the poor response rates, and these include perceptions that their diabetes would resolve after delivery of the baby, interpretation that the lack of reminder to reschedule missed appointments by their healthcare provider as indicators that they are at low risk of developing diabetes, as well as unpleasantness of the OGTT [28,36].…”
Section: Discussionmentioning
confidence: 99%
“…This theme was divided into two subthemes; time constraint and transport problem. In addition to colonoscopy, time constraint was also causing low adherence to other screening programs/tests (Brown et al, 2013;Mohd Suan, 2015;Waller et al, 2012). A tight schedule is more commonly observed among working patients.…”
Section: Logistic Obstaclesmentioning
confidence: 99%